Evaluation of Jacalin lectin sorbents for the extraction of the human chorionic gonadotropin glycoforms prior to analysis by nano liquid chromatography-high resolution mass spectrometry - Goumenou, Anastasia; Chendo, Christophe; Combès, Audrey; Fournier, Thierry; Pichon, Valérie; Delaunay, Nathalie (Journal of pharmaceutical and biomedical analysis, 2025)
Human chorionic gonadotropin (hCG) is a dimeric, highly glycosylated hormone with a total of 4 N- and 4 O-glycosylation sites in its two subunits, hCGα and hCGβ. Recently, we developed a novel nano liquid chromatography coupled to high resolution mass spectrometry (nanoLC-HRMS) method for the analysis and thus the detection of the intact glycoforms of hCG. Here, a sorbent functionalized with the Jacalin lectin was evaluated in solid-phase extraction (SPE) for its potential to fractionate the hCG glycoforms prior to their nanoLC-HRMS analysis at the intact level, which may facilitate the detection of low-abundance glycoforms and may lead to a more detailed characterization of the hormone glycosylation. A commercial sorbent based on Jacalin immobilized on Sepharose and having a lectin density of 4.5 mg per ml of gel was selected to carry out SPE and its capacity was estimated to be of some tens of μg of hCG per ml of lectin sorbent. Next, the SPE protocol was modified to improve the extraction recoveries. Especially, it was noticed that an extensive pre-conditioning procedure prior to the first use of a cartridge was necessary to remove the residual non-grafted lectins. Indeed, if non-grafted lectins are not eliminated, they may bind a part of hCG glycoforms preventing their retention by the sorbent, leading to low extraction recoveries (around 10 %). With the extensive pre-conditioning procedure, the average extraction recoveries for both hCGα and hCGβ glycoforms were about 50 %, with either recombinant or urinary hCG. Qualitatively, the fractionation of hCG glycoforms between the washing and elution fractions was achieved with the urinary hCG sample by determining the number of glycoforms detected in each fraction. It appears that 12 hCGα glycoforms have a low affinity (detected only in the washing fraction), 1 a low-medium affinity (detected in washing and elution 1 fractions), 16 a medium affinity (detected in washing, elution 1 and 2 fractions), and 12 a high affinity (detected only in elution 1 and 2 fractions). For the hCGβ glycoforms, similarly, 3 have a low affinity and 12 a low-medium affinity. Additionally, the 3 hCGβ glycoforms were detected better. A different behavior was observed with the recombinant hCG sample, which indicates glycosylation differences between the two hCG samples. This shows the potential of lectin-based affinity fractionation before nanoLC-HRMS analysis to better characterize the glycosylation state of hCG at the intact level. •Capacity of Jacalin sorbents were evaluated with recombinant and urinary hCG.•the SPE procedure was developed to improve extraction recoveries.•SPE with Jacalin sorbents led to recoveries of around 50 % for hCG glycoforms.•Jacalin SPE enabled fractionation of hCG glycoforms as a function of their affinity.•lectin SPE and intact protein analysis by nanoLC-HRMS improves hCG characterization.